Effects of the use ractopamine in pregnant sows on reproductive and blood parameters - Hoshi, E.H.=700 1 Fonseca, N.A.N.; Pinheiro, J.W.; Marcal, W.S.; Silva, C.A.
(Es, En)
ilus., 19 ref.
Keywords: CERDAS; GESTACION; SOMATOTROPINA; REPRODUCCION; ESPAÑA; BETA ADRENERGICO; PERFIL LIPIDICO; VALORES SANGUINEOS